2020
DOI: 10.3390/ijms21124219
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Induced Glioma Apoptosis through Noxa Upregulation

Abstract: Clinically, high cyclooxygenase-2 expression in malignant glioma correlates well with poor prognosis and the use of aspirin is associated with a reduced risk of glioma. To extend the current understanding of the apoptotic potential of aspirin in most cell types, this study provides evidence showing that aspirin induced glioma cell apoptosis and inhibited tumor growth, in vitro and in vivo. We found that the human H4 glioma cell-killing effects of aspirin involved mitochondria-mediated apoptosis accompanied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“… 40 In addition, mitochondria-mediated apoptosis was accompanied by BAX mitochondrial distribution and oligomerization, and caspase 3/caspase 8/caspase 9 activation. 41 This finding is consistent with our current results showing that the cleaved-caspase 3 activated and PI3K/AKT/mTOR signaling pathway were inhibited by the β-mangostin treatment.…”
Section: Discussionsupporting
confidence: 93%
“… 40 In addition, mitochondria-mediated apoptosis was accompanied by BAX mitochondrial distribution and oligomerization, and caspase 3/caspase 8/caspase 9 activation. 41 This finding is consistent with our current results showing that the cleaved-caspase 3 activated and PI3K/AKT/mTOR signaling pathway were inhibited by the β-mangostin treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Phosphodiesterase inhibitors increase the efficacy of anticancer drugs by promoting endocytosis-mediated cellular drug uptake [ 37 ]. We have demonstrated that aspirin induced endoplasmic reticulum stress-increased Noxa upregulation, restored ABT-737 apoptosis, and impaired glucose and glutamine metabolism in cancer cells [ 18 , 19 , 20 ]. In this study, aspirin and dipyridamole caused cell apoptosis and sensitized cells to doxorubicin-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned findings suggest that HMGB1 could be an action target of antiplatelet drugs involving the disruption of reciprocal interaction between platelets and cancer cells. Previously, we reported the anticancer effects of aspirin through apoptosis, growth arrest, metabolic inhibition, and platelet cargo reduction, such as soluble P-selectin (sP-selectin) and TGF- β1 [ 18 , 19 , 20 ]. To continue and extend our research concentrating on reciprocal crosstalk between platelets and cancer cells, as well as anticancer potential of antiplatelet drugs, human chronic myeloid leukemia K562 cell-differentiated megakaryocytes, human bladder cancer T24 cells, murine platelets, murine Lewis lung carcinoma (LLC) cells, and C57BL/6-LLC tumor-bearing mice models were established and subjected to antiplatelet drug treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, anti-glioma treatments cause ER stress and UPR. With extrinsic insults and intrinsic alterations, glioma cells become sensitized to ER stress, leading to apoptosis [ 15 , 16 , 17 , 18 , 19 ]. The lung cancer cells with EGFR inhibitor gefitinib-resistance express higher levels of GRP78, and lower levels of CHOP.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the alteration and role of ER stress in gefitinib-treated glioma cells remain unclear. In our previous studies on glioma cells, we reported that gefitinib induces apoptosis and autophagy, and the ER stress contributes to glioma apoptosis [ 15 , 16 , 22 , 23 , 24 ]. To extend the finding on ER stress, we conducted this study to determine the role of ER stress in gefitinib-induced glioma apoptosis, and identify the molecular basis underlying the UPR-committed apoptotic program.…”
Section: Introductionmentioning
confidence: 99%